Intellectual capital disclosure and corporate market value: Does board diversity matter? - Anifowose, Mutalib; Ab. Rashid, Hafiz Majdi; Annuar, Hairul Azlan (Emerald, 2017)
Purpose – The purpose of this paper is to examine the relationship between IC disclosure and the corporate market value (CMV) of listed firms on the main board of Nigeria Stock Exchange and to test the moderating effect of religious and ethnic composition of board members on the relationship. Design/methodology/approach – This study applies the signaling and upper echelons theories in formulating four hypotheses that guide the results analysis. By employing a two-step dynamic system generalized method of moments and controlling for the possible endogeneity effect on the parameters estimated for a sample of 91 listed firms on main board of Nigeria Stock Exchange, this study investigates the association of IC disclosure with CMV, namely, cost of capital and market capitalization, and the moderating role of religious and ethnic composition on such association using data over the 2010 to 2014 financial years. Findings – The results show a significant positive relationship between overall IC disclosure and market capitalization and a negative impact on cost of capital, which are in line with the hypothesized propositions. The moderating effect of board diversity is also confirmed. This study contributes to recent evidence concerning the value relevance of IC information to investors and other interested stakeholders and the established moderating role of board diversity in IC disclosure-related studies. Practical implications – The regulators may consider development of standards on board composition about religious and ethnic composition in order to curb the domination from same group in the board room. Those charged with governance should be concerned with the disclosure of IC information in the financial statements as it has value relevance to the investors, in line with signaling theory. Social implications – The ethnic and religious composition of board members is a significant factor within the board room and needs to be given adequate consideration. Originality/value – This study is the first to consider IC disclosure across whole sectors in the Nigerian economy and looks upon ethnicity and religious affiliation of boards as moderating variables. The study controls for heteroscedasticity and endogeneity issues by adopting two-step dynamic system generalized method of moments.